Application of the Intervention Mapping Protocol to Develop Sahtak bi Sahnak, a School-Based Intervention to Prevent Pediatric Obesity among Lebanese Adolescents. Issue 1 (2nd March 2021) - Said, Liliane; Schneider, Francine; Kremers, Stef P. J.; Gubbels, Jessica S.
Background: Pediatric obesity is a major public health concern worldwide. Improving dietary and physical activity habits at a young age could prevent many health complications during adulthood and later years. Objective: This paper describes the application of the Intervention Mapping protocol for the systematic development of the Lebanese intervention "Sahtak bi Sahnak" (meaning Your health in your plate) that focuses on preventing pediatric obesity and promoting a healthy lifestyle through a systematically designed and culturally appropriate, school-based program. Method: The development of this intervention is based on the six steps of the Intervention Mapping (IM) protocol. This intervention targets Lebanese adolescents aged 15–18 years enrolled in Lebanese public and private high schools, located in urban and rural areas. Its effectiveness will be tested in a Clustered Randomized Controlled Trial in 16 high schools. Discussion and conclusion: The IM protocol allowed us to develop a theory based, low resource intervention which can be integrated as part of the educational curriculum of public and private high schools in Lebanon. This study provides a detailed example of the application of the IM approach in the Lebanese high school context. Even though it is a time-consuming process, IM serves as a valuable tool in the health promotion field and provides a high level of transparency to improve and replicate the process in the future.